(untitled) (MAUSAM, 2007)
Kharif and Rabi rice grown extensively over Kerala is mainly infested by gall midge, leaf folder and green jassid in kharif season. Under favourable weather conditions leaf folder become the dreaded pest and cause considerable damage to the crop. The study revealed that maximum and minimum temperature, morning and afternoon relative humidity and weekly total of rainfall have profound effect on the development of leaf folder at their successive generations on kharif rice crop. Weather based multiple regression models for the peak infestation period for each of the generations of the pest were developed using data for the period 1987-99 and validated using observed meteorological as well as pest data for 2000-2001. Based on the findings of this study pest weather calendar for leaf folder of kharif rice was prepared. This calendar would be useful for early warning and operational rice crop protection from leaf folder attack.